PENGARUH MODEL PEMBELAJARAN TEACHING FACTORY TERHADAP KEMAMPUAN KOMUNIKATIF DAN KETERAMPILAN KOLABORATIF SISWA KELAS XI JURUSAN TEKNIK PERMESINAN SMK NEGERI 2 SAMPANG - Jamaluddin, Dzikrullah; Sucipto; Isman, Soubar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The objectives of this research include: 1) To determine the influence of the teaching factory learning model on the communicative abilities of class Sampang, and 3) To determine the effect of the teaching factory learning model on the communicative and collaborative abilities of class XI students majoring in Mechanical Engineering at SMK Negeri 2 Sampang. This research is a quantitative experimental research where the researcher made all class XI TP students as research subjects, namely class XI TP-1 students as many as 32 male students as the control group and class. Researchers used communicative questionnaires and collaborative questionnaires. Based on the results of the analysis using the MANOVA analysis technique, it was concluded that: 1) There is an influence of the teaching factory learning model on the communicative abilities of class SMK Negeri 2 Sampang, and 3) There is an influence of the teaching factory learning model on the communicative and collaborative abilities of class XI students majoring in Mechanical Engineering at SMK Negeri 2 Sampang.